Systematic Literature Review (SLR): Implementation of the School Literacy Movement (GLS) Programme on Critical Thinking in Primary School Indonesian Learning Outcomes - Gadis Niyanti Pertiwi; Dase Erwin Juansah (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Reading literacy is not just about being able to spell or read, but it is also a very important skill in learning and everyday life. By having this ability, a person can understand and then be able to obtain information more effectively, develop knowledge, and understand other people's perspectives and experiences that can enrich their thinking and broaden their scientific horizons. This research on the implementation of the GLS programme aims to conduct a literature review on the implementation of the School Literacy Movement (GLS) programme in primary schools. In this study, researchers referred to articles or journals using the keyword ‘School Literacy Movement’ in the Google Scholar database. This research was conducted with stages, starting from article collection, article reduction, presentation, and discussion. This article is the result of an analysis based on the literature on the subject being discussed. The research method used in this study is the SLR (Systematic Literature Review) method. The findings of the SLR study which analysed 15 articles showed that the School Literacy Movement must start early, starting from habituation development, and implementation, and the role of parents should not be ignored in the implementation of this GLS.